PENGAWASAN INTERNAL TERHADAP DISIPLIN KERJA PEGAWAI PT. POS INDONESIA (PERSERO) UNIT SUDIRMAN KOTA PEKANBARU TAHUN 2018. - Saralawati, Dwi Putri; M, Erman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
PT. Pos Indonesia (Persero) is one of the largest state-owned enterprises (BUMN) in Indonesia. PT. Pos Indonesia has many branches in Indonesia and has many employees, including PT. Pos Indonesia Sudirman Unit Pekanbaru City is the center of the Post Office in Pekanbaru. PT. Pos Indonesia Sudirman Unit Pekanbaru City which from year to year has decreased the level of employee work discipline due to lack of supervision conducted.This study aims to find out how internal control over the work discipline of PT. Pos Indonesia (Persero) Unit Sudirman City of Pekanbaru, then also to find out the factors that affect the work discipline of employees in PT. Pos Indonesia Sudirman Unit Pekanbaru City. The location of the study was conducted in Pekanbaru, PT. Pos Indonesia Jalan Sudirman. Furthermore, data collection techniques were carried out by interview, documentation and literature study.The results of this study are the Internal Control of Employee Work Discipline of PT. Pos Indonesia Sudirman Unit Pekanbaru City has not been running optimally. This is caused by several factors such as the size of compensation. *Keywords: Supervision, Internal Oversight, Work Discipline, Employees